Developing a measure of mental health service satisfaction for use in low income countries: a mixed methods study - Mayston, Rosie (BMC Health Serv Res, 2017)
BACKGROUND: Service satisfaction is integral to quality of care and measures are therefore considered important indicators of quality. Patient’s responses to their experiences of using services are under-researched in the context of mental healthcare in low income countries. Our aim was to use mixed methods to develop a new measure of satisfaction for use among consumers of the new models of mental healthcare which are currently being scaled-up. METHODS: We used qualitative methods to explore the concept of service satisfaction. On the basis of these findings, we developed a new ‘Mental health service satisfaction scale’ (MHSSS v0.0) by adapting existing measures of service satisfaction. We evaluated psychometric properties of the new measure, among a sample of service users with severe mental disorder (SMD) (n = 200) and caregivers (n = 200). Following expert review, a modified version of the measure was developed (MHSSS v1.0) and psychometric properties were examined with data from a second independent sample (n = 150 service users with SMD and n = 150 caregivers). RESULTS: Factors identified in analysis of the first quantitative sample coincide with core concepts of service satisfaction as reported in the literature and were reflected in the key themes which emerged from our qualitative study: interpersonal factors, efficacy, communication, technical competency and adequacy of facilities. There was generally consensus among caregivers and service users regarding dimensions of satisfaction. However there was evidence of some differences in prioritization. Revisions made to version 0.0 of the Mental Health Service Satisfaction Scale (MHSSS) led to an improved instrument, with excellent internal consistency, convergent validity and factor loadings indicative of a uni-dimensional construct. CONCLUSIONS: Our findings suggest that conceptions of service satisfaction among people accessing a service for SMD are broadly similar with those established in the literature. Our findings indicate that the MHSSS might be a useful candidate for inclusion in the new toolkit of measures needed to facilitate monitoring of service satisfaction which will be crucial to quality improvement. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-017-2126-2) contains supplementary material, which is available to authorized users.